Improvement of Credit Processing Model of Commercial Banks on the Scale Scale System - Norov Akmal Ruzimamatovich (Research Parks Publishing LLC, 2022)
The article describes a new model of compliance with the terms of credit of business entities by commercial banks and its evaluation. In this regard, the advantages of the